Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1034/j.1399-6576.2002.460713.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propofol on cerebral blood flow and the metabolic rate of oxygen in humans

Abstract: Propofol proportionally decreased CBF and CMRO2 without affecting a-vDO2 in humans, suggesting that normal cerebral circulation and metabolism are maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 31 publications
(48 reference statements)
6
69
1
Order By: Relevance
“…It is known that altered neurometabolic dynamics can occur in each of the conditions associated with burst suppression: in general anesthesia, through a reduction in neural activity and subsequent reductions in CMRO (25,36); in hypoxic/ischemic injury, through aberrant reductions in metabolic regulation due to diffuse injury or through direct oxidative stress (6,22); in hypothermia, through direct reductions in metabolic rate (3,35); and in developmental encephalopathy, through neural and metabolic dysfunction (23). Implicating brain metabolism in the neural mechanisms of burst suppression establishes a unifying physiologic connection between the main etiologies of the phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that altered neurometabolic dynamics can occur in each of the conditions associated with burst suppression: in general anesthesia, through a reduction in neural activity and subsequent reductions in CMRO (25,36); in hypoxic/ischemic injury, through aberrant reductions in metabolic regulation due to diffuse injury or through direct oxidative stress (6,22); in hypothermia, through direct reductions in metabolic rate (3,35); and in developmental encephalopathy, through neural and metabolic dysfunction (23). Implicating brain metabolism in the neural mechanisms of burst suppression establishes a unifying physiologic connection between the main etiologies of the phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The parameter J ATP is the production rate of ATP that is known to be directly coupled to the cerebral metabolic rate (32). As a surrogate for the metabolic rate, we directly manipulate J ATP over a range of 30−50% of baseline, consistent with studies of anesthetic and hypothermic effects on cerebral metabolism (35,36). Complete details of the model and simulation parameters are found in SI Methods.…”
Section: Methodsmentioning
confidence: 99%
“…The change in the a-vDO 2 also indicates a resetting of the relationship between CMRO 2 and CBF. Several studies have found an unchanged a-vDO 2 in healthy subjects during propofol sedation, 25,26 even at doses leading to an isoelectric electroencephalogram. 27 Taken together, the results suggest that cerebral metabolic coupling is impaired in patients with bacterial meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with severe BAE can have increased intracranial pressure due to hypercapnia, and unconscious patients with increased intracranial pressure can have worse outcomes if ETI is performed without appropriate premedication [27]. Propofol is an attractive choice for premedication in this scenario because it can decrease intracranial pressure [28][29][30].…”
Section: Attenuation Of the Risks Of Eti-related Adverse Events In Bamentioning
confidence: 99%